2014
DOI: 10.1371/journal.pone.0094207
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of the Patient-Clinician Relationship on Healthcare Outcomes: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: ObjectiveTo determine whether the patient-clinician relationship has a beneficial effect on either objective or validated subjective healthcare outcomes.DesignSystematic review and meta-analysis.Data SourcesElectronic databases EMBASE and MEDLINE and the reference sections of previous reviews.Eligibility Criteria for Selecting StudiesIncluded studies were randomized controlled trials (RCTs) in adult patients in which the patient-clinician relationship was systematically manipulated and healthcare outcomes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
473
1
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(503 citation statements)
references
References 38 publications
16
473
1
13
Order By: Relevance
“…Multiple studies have shown that communication skills can be improved with effective training, and that effective communication improves medical outcomes, safety, patient adherence, patient satisfaction, and provider satisfaction and efficiency. [5][6][7][8][9][10][11][12][13][14] Organization-wide communication skills improvement programs are rare and reports are limited to case studies. 15 We designed and implemented an experiential, relationship-centered communication skills course and measured its impact on patient satisfaction, physician empathy, burnout, and self-efficacy in a large, multispecialty academic medical center.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that communication skills can be improved with effective training, and that effective communication improves medical outcomes, safety, patient adherence, patient satisfaction, and provider satisfaction and efficiency. [5][6][7][8][9][10][11][12][13][14] Organization-wide communication skills improvement programs are rare and reports are limited to case studies. 15 We designed and implemented an experiential, relationship-centered communication skills course and measured its impact on patient satisfaction, physician empathy, burnout, and self-efficacy in a large, multispecialty academic medical center.…”
Section: Introductionmentioning
confidence: 99%
“…Clinician empathy improves both objective and subjective health care outcomes. 3,4 It is positively related to patient confidence in health care professionals and to patient compliance with treatment. 5,6 Empathy is also positively associated with the clinical competence of medical students and with the quality of their patient interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and metaanalysis of 13 randomized controlled trials on the patient-physician relationship found that the quality of the therapeutic alliance had a positive effect on health outcomes [7]. Importantly, the impact of the patient-physician relationship on health outcomes was greater than that found in other studies of common interventions, including aspirin for reducing the risk of recurrent myocardial infarction over five years and the influence of smoking on male mortality over eight years [8].…”
Section: Physicians' Duty To Treatmentioning
confidence: 98%